The microbiota diversity of Festuca sinensis seeds in Qinghai-Tibet Plateau and their relationship with environments - Gao, Yue; Chen, Youjun; Luo, Yang; Liu, Junying; Tian, Pei; Nan, Zhibiao; Zhou, Qingping (Frontiers in Microbiology, 2022)
Fourteen Festuca sinensis seed lots were collected from different geographical locations on the Qinghai-Tibet Plateau to study the seed microbiota and determine the abiotic (temperature, precipitation, and elevation) and biotic (Epichloë sinensis infection rate) factors likely to shape the seed microbiome. The 14 seed lots had different bacterial and fungal structures and significantly different diversities (P<0.05). The α-diversity indices of the bacteria were significantly correlated with precipitation (P<0.05), whereas those of the fungi were significantly correlated with temperature (P<0.05). Microbiota analysis showed that Proteobacteria, Cyanobacteria, and Bacteroidetes were the most abundant bacteria at the phylum level in the seeds, and Ascomycota and Basidiomycota were the most abundant fungi. β-diversity analysis suggested large differences in the microbial communities of each sample. Redundancy analysis showed that temperature and precipitation were the main environmental factors driving variations in the microbial community, at the medium-high elevation (3000-4500 m), the impact of temperature and precipitation on microbial community is different, the other elevations which effects on microbial community were basically identical. Spearman correlation analysis showed that the relative abundances of the most abundant bacterial phyla were significantly correlated with temperature (P<0.05), whereas those of the most abundant fungal phyla were significantly correlated with precipitation (P<0.05). E. sinensis infection rates were significantly correlated with elevation and temperature (P<0.05). These results suggest that temperature and precipitation are the key factors driving the microbial community, that temperature and elevation also had a great influence on the E. sinensis infection rate, and that environmental factors (temperature and elevation) may further affect the microbial community by regulating the E. sinensis infection rate.